Determination of Source of Gold around Itagunmodi Southwest, Nigeria - Bello, A. K.; Adetoyinbo, A. A. (Darul Yasin Al Sys, 2025)
The source of gold mineralization had been a subject of proposal in the past; some researchers suggested its original source to be the crust while some proposed the source as the mantle. In this study, the source of gold in Itagunmodi was the main objective. The melting temperature of gold and the variation of melting temperature with increase in pressures were determined from melting temperature equations and the values were correlated with the stress in the lithosphere to determine the source. At high values of pressures, the gold melts at higher temperatures. The melting temperatures ranged between 1064 ℃ to 1394.3 ℃ while pressure ranged between 2605.68-2931.39 MPα, (i.e 26-29 Kbar). When merged with the temperature and stress field in the Earth, its shows that the source of gold mineralization around the location is the mantle part of the lithosphere and this can serve as the baseline to the source of gold which was believed to originate from the mantle.